Determination of Physical Properties of Polymeric and Different Additives on Bituminous Binders - Seza Deveci, Isra; Yilmaz, Mehmet (ISRES Publishing, 2025)
This study was designed to comprehensively investigate the diverse and complex effects of polymeric and reactive additives on asphalt binders, employing a thorough experimental methodology rooted in conventional binder testing techniques. Unlike many previous studies that focus on a limited selection of additive types, this research extended its scope by comparatively analyzing various elastomeric and chemical additives, all tested on the same base bitumen under a single, standardized procedure. Evaluations were systematically conducted based on results from conventional binder tests. The experimental findings revealed that the Enprene 611 additive significantly enhances high-temperature performance, while the CR additive contributes markedly to improving low-temperature flexibility and resistance to cracking. This comparative methodology, which is rarely observed in existing literature, sheds light on how different additive types influence the mechanical and rheological properties of asphalt binders. By exploring both performance aspects, this research offers a unique and innovative perspective that could guide future developments in asphalt technologies and support the creation of more durable pavements under diverse climatic and loading conditions. © 2025 Published by ISRES Publishing: www.isres.org.
5th International Conference on Basic Sciences and Technology, ICBAST 2025 -- 28 August 2025 through 31 August 2025 -- Budapest -- 344359
Keywords: Asphalt; Bitumen; Modification; Polymer; Softing point